USULAN PENATAAN ULANG FASILITAS UKM BINAR PIGURA MENGGUNAKAN METODE ARC - utomo, dibyo adi (Universitas Muhammadiyah Gresik, 2024)
This study examines the organization of facilities at Binar Pigura SME, a small and medium enterprise that produces pigura in Lamongan. This research focuses on production activities, layout, data processing, and layout design of SME facilities. The method used is the Activity Relationship Chart (ARC) developed by Richard Muther in 1973. Data were obtained through literature and field studies. The results showed that the production activities at Binar Pigura SME involved making frames from cutting the frame rod material, assembling the frame rods, to finishing the frame products. The redesign of the facility layout with the ARC method results in a new placement based on the relationship of the degree of closeness of the facility using the ARC method, the calculation of the total distance traveled in the frequency of 1 production unit of the pigura total distance generated by the alternative layout with the result of 6.68 meters. Compared to the total mileage of the initial layout which amounted to 16.5 meters, with an alternative layout, a distance reduction of 59.51% was obtained.